2020
DOI: 10.1177/1747954120964059
|View full text |Cite
|
Sign up to set email alerts
|

Dark traits as a potential feature of leadership in the high-performance sports coach

Abstract: High-performance sport coaches are leaders in their field; therefore, they sometimes operate under ‘regular’ workplace leadership role requirements. However, they are also subject to highly uncertain and pressured environments. Thus, most coaching/leadership positions in high-performance sport may be both ‘normal’ and ‘unique’ in leadership role requirement. Consequently, understanding what high-performance sport leaders ‘look like’, behaviorally, would be valuable. This study aimed to 1) describe personality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Previous work has linked this right and left hand 2D:4D difference to reactive aggression and masculinity (i.e., previous work has linked 2D:4D to being more “male like”; Coyne et al, 2007 ; Kilduff et al, 2013a ). Aggression is considered a trait behavior ( Serpell et al, 2020a ). Journalism is a highly competitive field and often involves physical and psychological jostling for priority to stories, however, it would be hard to compare the so-called media scrum to an actual professional rugby scrum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has linked this right and left hand 2D:4D difference to reactive aggression and masculinity (i.e., previous work has linked 2D:4D to being more “male like”; Coyne et al, 2007 ; Kilduff et al, 2013a ). Aggression is considered a trait behavior ( Serpell et al, 2020a ). Journalism is a highly competitive field and often involves physical and psychological jostling for priority to stories, however, it would be hard to compare the so-called media scrum to an actual professional rugby scrum.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Further, the current narrow definitions of what good coaching ‘looks like’ is being challenged where the traditional technical and tactical expertise of a HP coach now needs to be supplemented with a strong capacity for learning and exceptional leadership capability. 4,6,7 That is, technical expertise in sport is no longer enough to discriminate between ‘quality’ of coaches. Thus, work which provides insights into coach success and development is demanded; and, as already alluded, and will be discussed throughout this paper, this particularly the case for people who come from ‘diverse’ backgrounds – including women.…”
Section: Introductionmentioning
confidence: 99%
“…14 Clearly defining the role of the coach and a contemporary job paradigm to meet the future needs of sports and athletes. 4 While not all of these issues for women are present in all HP sport environments, evidence would suggest they remain in many. By addressing these issues, the opportunity could be to create environments that foster a variety of coaching styles and philosophies (and potentially competitive edge), as well as increasing the volume of ‘good’ coaches across all HP sports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, it is also worth noting that recent work, describing the personality traits of elite coaches reported that they may be uncommunicative, moody, hard to please, and limit-testing. 12 These traits may make it difficult for scientists to communicate effectively with coaches and limits mutual understanding. Moreover, research has shown that communication styles and knowledge differences between coaches and sports scientists impeded elite sprinters’ performance improvements.…”
Section: Introductionmentioning
confidence: 99%